Effect of anode distance on built-up edge in textured tools produced by plasma focus - Teh, Thiam Oun; Arwinder, Singh; Heng, B.K.; Wong, J.W.; Saw, S. H.; Lee, S. (INTI International University, 2021)
In this paper, the concept of producing a textured tool from AISI304 stainless steel with a plasma focus machine is investigated. A nitrogen ion beam is aimed at a steel sample in an effort to harden it by nitriding and thus render it suitable for use a cutting tool. The results show that the hardness is only slightly enhanced. However, the pitted surface caused by the ion beam gives the steel sample a surface texture that is suitable for a film of solid lubricant to anchor itself. This leads to a decrease in the formation of the built-up edge when performing a dry cutting process on a ductile material such as aluminium. In this dry cutting process, a built-up edge of aluminium material tends to form and adhere to the steel cutting edge and this affects the overall performance of the steel tool. By varying the distance of the anode to the steel tool in the plasma focus nitriding process and then measuring the corresponding amount of built-up edge formed, it is found that, at shorter anode distances, the built-up edge effect is less pronounced.